Auditoría operativa al área de inventarios y su incidencia en la rentabilidad de la ferretería Barros, cantón Buena Fe, año 2013 - Enderica Rivera, Cecilia Ivonne (2016)
This research was conducted in the Hardware Barros, located in Canton Buena Fe, Av. August 7 and Mariana Rodriguez, which main objective was to conduct a performance audit inventory area to determine its impact on profitability the aforementioned company, 2013, in the development of this was necessary to have an appropriate methodology as deductive, analytical and statistical methods complemented by types such as field research, bibliographic and documentary techniques and instrument evaluation as observation and interview within the research design was performed by planning, execution and reporting, in complement to this work order, notice of initiation, report previous visit, it was developed an audit program along with it was used the questionnaire control Internal using the COSO II model that lead to knowledge of the efficiency and effectiveness of the company, during this assessment calculations were made to find the inherent risk, control confirming have a high confidence with 90.63% and 9.37% risk control by number of findings as no manual functions detected, the shelves do not have labels or codes storage, weak control in the process of receiving, too much space in the hallways, insufficient storage pallets, after these results it was concluded that There have acceptable control within the company, you do not have optimal information system for procurement activities, weaknesses in logistics management occurred due to insufficient evaluation of the processes involved in the area, the end result This evaluation indicated in the reports for each process developed, which will help managers to correct situations that affect the operations of the entity.